Specificities of measured polyvariance the seeds of Cucurbita pepo var. giramontia Duch. under climate changes in Pridnestrovie - V. F. Khlebnikov; N. V. Smurova; I. T. Balashova (Овощи России, 2020)
Actuality. Industrial technologies of vegetable crops cultivation, including squash cultivation, a lot of attention is paid to the uniformity of seeds by morphometric traits as a condition allowing to use the precision technologies.The goal of the study is to determine specificities of measured polyvariance the seeds of Cucurbita pepo var. giramontia Duch. under changes of climate conditions in Transnistria.Materials and methods. The studies were carried out at the experimental plot of Pridnestrovian State University (Tiraspol) in 2005-2012. Objects of studies – 5 lines (166/5; 19/84; 98/5; 5Б; 48/20) of squash. Morphometric traits of seeds: mass, width, length, thickness were evaluated in the sample of 100 seeds. Mass of the seed was evaluated with help of torsion scales with exactness to 0,001 g. Width, length, thickness were mesuared with microscope MBS-10 with exactness to 0,1 mm. squash plants were treated with water solutions of the preperation Micefit in concentrations 10 and 100 mg/l in the phase of "2-3 true leaves" and "6-7 true leaves", standard is water treatment.Meteorological conditions (temperature, amount of precipitation) the year of seed reproduction were characterized by the data of Tiraspol Agrometeorological Station. Hydrothermal regime the growing of squash plants was characterized by the hydrothermal coefficient (CHT) of Selyaninov.Results. The nature of changes in temperature and precipitation over 7 years (2005-2012 periods) were reflected increased anomality of weather conditions in Transnistrian region. First of all, it concerns the quantity and the intensity of precipitation during the formation and maturation of squash seeds. Distribution decades of total precipitation and temperatures caused extremely uneven hydration: CHT variation ratio was 29.2-61.3%. Almost all periods of study were stressful for plants and led to the dimensional polyvariance of squash seeds. The variation of morphometric traits (coefficient of variation) is depended on changes in the hydrothermal regime of the growing season. It has a non-linear character and was genotypically caused. Applying the preparation Micefit had a significant effect on the manifestation of traits of squash seeds and its interaction with meteorological factors determined their modifying ability in the following order: mass (78,2%)→ length (56,6%)→ thickness (43,7%)→ width (40,4%).